Three new species of Collembola from north-east Italy - Fanciulli, Pietro Paolo; Dallai, Romano (Zootaxa, 2008)
Three new species of Collembola belonging to three different families were described from the Cansiglio Natural Reserve (north-east Italy): Hypogastrura pizzoci sp. nov. (Hypogastruridae), Endonura saleri sp. nov. (Neanuridae) and Pseudosinella cansiliensis sp. nov. (Entomobryidae).